NERDS : National Espionage, Rescue, and Defense Society - Buckley, Michael; Beavers, Ethen (New York : Amulet Books, 2009)
While running a spy network from their elementary school, five unpopular misfits combine their talents and use cutting-edge gadgetry to fight evil around the world.
Keywords: Spy stories; Schools -- Juvenile fiction; Humorous fiction